2015
DOI: 10.1186/s12916-014-0246-7
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and blood transfusion in African children presenting to hospital with severe febrile illness

Abstract: Background: Severe anaemia in children is a leading cause of hospital admission and a major cause of mortality in sub-Saharan Africa, yet there are limited published data on blood transfusion in this vulnerable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(139 citation statements)
references
References 28 publications
4
130
5
Order By: Relevance
“…In this study, almost half of all patients were transfused including 94% of those with severe anemia. 9 The mean age of children that received blood transfusions in this study (2.5) is lower than that of the Children's hospital (5.5) in Washington. Children in Africa are obviously exposed to diseases that predispose them to anemia and malaria at an early age when compared with children in developed countries.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In this study, almost half of all patients were transfused including 94% of those with severe anemia. 9 The mean age of children that received blood transfusions in this study (2.5) is lower than that of the Children's hospital (5.5) in Washington. Children in Africa are obviously exposed to diseases that predispose them to anemia and malaria at an early age when compared with children in developed countries.…”
Section: Discussionmentioning
confidence: 52%
“…13,16 In the study carried out among children presenting to six hospitals in malaria-endemic regions of Uganda, Kenya, and Tanzania, malaria parasitemia was present in 57% of children, with a higher proportion of anemic children having parasitemia compared with non-anemic children. 9 This might be considered as one of the reasons why most children with malaria infection have more blood transfusions than those without malaria infection. In this study, the most common symptoms of malaria recorded were fever and gastrointestinal symptoms; this thus explains why these symptoms were seen in most of the children who had blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid identification of severe anaemia is of particular importance because aggressive crystalloid infusion is associated with increased morbidity and mortality among these patients 18. In a secondary analysis of a large multicentre clinical trial conducted in east Africa, Kiguli et al 19 found that severe anaemia was present in one-third of patients and was associated with increased mortality, with many deaths occurring within 2.5 h of presentation. As such, accurate clinical recognition of the presence and severity of anaemia can help guide the implementation of specific resuscitative strategies in a timely fashion to ensure optimal patients outcome.…”
Section: Discussionmentioning
confidence: 99%